Interprofessional Shared Decision-Making: Assessment of Behavioral Intention Though a Tool Based on the Theory Planned Behavior - Jamileh Salar; Fatemeh Keshmiri (Kerman University of Medical Sciences, 2018)
Objectives The present study was conducted with the aim of psychometric evaluation of a tool measuring behavioral intention in relation to interprofessional shared decision-making based on the theory of planned behavior and its assessment among medical and nursing students. Methods This descriptive study was carried out in two stages. In the first stage, the psychometric properties of the interprofessional shared decision-making (IP-SDM) tool were evaluated based on experts' opinions. In the second stage, the participants' behavioral intention was evaluated using the mentioned questionnaire. The questionnaire consisted of five domains of cognitive attitude (2 items), emotional attitude (2 items), subjective norms (3 items), perceived behavioral control (3 items), and intention to use interprofessional shared decision-making (3 items). Content validity of the questionnaire was evaluated qualitatively and quantitatively (using the content validity ratio (CVR) and content validity index (CVI)). Cronbach's alpha coefficient and interclass correlation coefficient (ICC) were used to determine the reliability of the questionnaire. In the second stage, the data were analyzed using descriptive statistics (mean and standard deviation) and Pearson's correlation test in SPSS software. Results Qualitative and quantitative content validity of the questionnaire was confirmed based on experts' opinions. The internal consistency of the tool, based on the Cronbach's alpha coefficient, was 0.92, and the tool's repeatability was calculated at 0.84 using ICC. Participants in the study intended to participate in interprofessional shared decision-making. Conclusions The behavioral intention measurement tool in relation to interprofessional shared decision-making based on the theory of planned behavior has good validity and reliability in Iran. Regarding the participants' behavioral intention to participate in shared decision-making, it is suggested that a suitable platform for shared decision-making and teamwork between health team members be provided in educational systems.